2007
DOI: 10.1007/s10038-007-0186-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations and haplotype structures of the DPYD gene encoding dihydropyrimidine dehydrogenase in Japanese and their ethnic differences

Abstract: Dihydropyrimidine dehydrogenase (DPD) is an inactivating and rate-limiting enzyme for 5-fluorouracil (5-FU), and its deficiency is associated with a risk for developing a severe or fatal toxicity to 5-FU. In this study, to search for genetic variations of DPYD encoding DPD in Japanese, the putative promoter region, all exons, and flanking introns of DPYD were sequenced from 341 subjects including cancer patients treated with 5-FU. Fifty-five genetic variations, including 38 novel ones, were found and consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 28 publications
3
43
0
Order By: Relevance
“…Statistically significant difference between controls and the high-toxicity group was found in frequency of IVS14+1G>A carriers The DHPLC analysis performed in the low-toxicity and control groups revealed presence of five intronic variants flanking to analyzed exons (IVS9-51T>G, IVS10-15T>C, IVS12-11G>A, IVS13+39C>T, and IVS13+40A>G). All these variants of unknown significance were described previously in various populations and were not considered for further analysis in our study [12,24,25]. The strong association of IVS13+39C>T with c.1627A>G (I543V) reported in previous studies was also observed in our samples (data not shown) [16,26].…”
Section: Dpyd Alterations In the Group Of High-toxicity Patientssupporting
confidence: 68%
See 2 more Smart Citations
“…Statistically significant difference between controls and the high-toxicity group was found in frequency of IVS14+1G>A carriers The DHPLC analysis performed in the low-toxicity and control groups revealed presence of five intronic variants flanking to analyzed exons (IVS9-51T>G, IVS10-15T>C, IVS12-11G>A, IVS13+39C>T, and IVS13+40A>G). All these variants of unknown significance were described previously in various populations and were not considered for further analysis in our study [12,24,25]. The strong association of IVS13+39C>T with c.1627A>G (I543V) reported in previous studies was also observed in our samples (data not shown) [16,26].…”
Section: Dpyd Alterations In the Group Of High-toxicity Patientssupporting
confidence: 68%
“…Numerous DPYD alterations were reported in published studies and case reports, however the vast majority represents missense gene variants with unknown impact on DPD enzyme activity. Moreover, the strong population differences in frequency of common DPYD gene alterations and haplotypes were described [12]. Recently, the common fragile site FRA1E was localized in DPYD gene, however the large deletions in DPYD were not studied so far [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, multiple case reports (21)(22)(23)(24)(25)(26)(27), retrospective investigations (28)(29)(30), and prospective pharmacogenetic trials (31)(32)(33)(34) have shown a significantly increased inborn risk for severe, potentially lethal toxicity for IVS14þ1G>A hetero-and homozygotic patients, when given standard doses of fluoropyrimidine drugs, although a few studies could not confirm this association (35). Besides IVS14þ1G>A, more than 50 other polymorphisms in DPYD have been identified to date (36,37). Although very few of these polymorphisms have been associated with increased risk for toxicity, the clinical relevance for the majority of these polymorphisms is low or unclear.…”
Section: Introductionmentioning
confidence: 99%
“…About 3%-5% of the population has a (partial) DPD deficiency, which increases the risk for 5-FU-induced severe toxicity in these individuals [120]. Currently, Ͼ50 polymorphisms in DPYD, the gene encoding DPD, have been identified [121]. The most predominant polymorphism associated with DPD deficiency is IVS14ϩ1GϾA (DPYD*2A).…”
Section: Dpdmentioning
confidence: 99%